Penambahan Enzim Sawit Dalam Pakan Yang Berbeda Terhadap Performa Ayam Broiler - Idham Noviandi; Fita Ridhana; Erita; Nasrullah (JURNAL RISET RUMPUN ILMU HEWANI, 2022)
Addition of Palm Enzymes in with Different Variations in Chicken Performance of Undergraduate. The purpose of this study was to determine the effect of giving palm oil enzymes to the weight gain of broiler chickens. the consumption of broiler chicken feed. To determine the administration of palm enzymes influence the increase in broiler chicken feed conversion. The design used in this study was a Completely Randomized Design (CRD), the provision of Palm Enzymes and without the provision of Palm Enzymes. By giving chicken ration given to Broiler Chicken P0: Without the addition of 0% palm enzyme (control), P1: addition of 25 ml palm enzyme + 75 commercial feed, P2: addition of 50 ml palm enzyme + 50 commercial feed P3: addition of palm enzyme 75 ml + 25 commercial feed. On the parameters of observation of body weight, feed consumption and broiler chicken feed conversion obtained during the study were best found in treatment P1: addition of 25 ml palm enzyme + 75 commercial feed. In the sidik analysis, the various effects of body weight, feed consumption and feed conversion between treatments different significantly.